Wireless fire detection system with GIS technology for fire and rescue application / Salihin Azmil - Azmil, Salihin (2016)
The mission of the Fire and Rescue Service is to protect lives, properties and natural resources from fire and other emergencies. With increasing demands, the Fire and Rescue Service must utilize the best tools, techniques, and training methods to meet public expectations. As a result, three-Dimensional (3D) city and building models for Fire and Rescue Applications have become an important part of Geographic lnformation Systems (GIS) analysis Many airports, office buildings and department stores have complex floor plans, In such environments, most of normal map is not sufficient and time consuming in helping the Fire Fighter to navigate during fire emergency. To overcome this problem, a 3D network analysis of a building for Fire and Rescue Applications which is based on a 3D model of Faculty of Electrical Engineering building (FKE) in MARA University of Technology (UiTM), Shah Alam were designed based on a 3D model. This 3D network analysis model identifies the shortest path from the Fire and Rescue Service position to the source of emergency. It also designs a wireless fire detection system to help fire-fighters to pinpoint the emergency call location, assess the potential consequences, and determine the most efficient strategy. The 3D model was built by Google Sketch Pro 8 and the 3D network analysis was mainly conducted in the ESRI‘s ArcGIS software. The wireless fire detection systems were designed using Arduino Microcontroller. The 3D network analysis was based on distance measurements instead. The distance of each path was measured on the site personally for maximum accuracy. The fire detection systems prototype hardware are equipped with smoke sensor, image sensor, a transmitter and a receiver. This thesis is expected to help the Fire and Rescue Service in their mission by providing the shortest path to the source of emergency and hopefully, it will help in improving their response, adequate planning and preparedness. As a result, 3D map from 015 will help the fire fighter in their navigation in complex and confuse building plan, Information on Geographical feature for example route length and estimated time of arrival provided in the map will be beneficial in emergency operation. The fire fighter will also get the inside visual and the location of emergency area as the image and smoke sensor were both installed in the wireless fire detection device.